UPAYA KEPALA MADRASAH DALAM MEMBINA DAN MENINGKATKAN PROFESIONALITAS GURU MADRASAH TSANAWIYAH HIDAYATUL MUBTADIIN JATI AGUNG LAMPUNG SELATAN - Jewitra Rahmah Puspita (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
This research aims to investigate the school principal’s efforts in fostering and developing teacher professionalism. In an effort to improve the quality of education, many educational institutions have provided training and coaching. This study aims to measure whether such training has a positive impact on teacher professionalism. The research results showed that teachers who took part in coaching and development had significant improvements in teaching skills compared to the control group. They are better able to plan effective learning, manage the class well, and interact with students positively. Apart from that, they also have a higher level of motivation in teaching. These findings indicate that the efforts made by school principals can have a significant positive impact on teachers’ teaching skills. Therefore, it is recommended that educational institutions continue to encourage and provide coaching and development that is relevant and beneficial to their teachers. This can contribute to improving the quality of education and student learning experiences.